Geodesic Lightlike Submanifolds of Indefinite Kenmotsu Manifolds. (14th November 2012) - Haider, S. M. Khursheed; Thakur, Mamta; Advin,
Abstract : The aim of the present paper is to study geodesic contact screen Cauchy Riemannian (SCR-) lightlike submanifolds, geodesic screen transversal lightlike, and geodesic transversal lightlike submanifolds of indefinite Kenmotsu manifolds.